Destination Image of Kyrgyzstan: A Content Analysis of Travel Blogs. Issue 5 (3rd September 2022) - Aitieva, Dinara; Kim, Sehun; Kudaibergenov, Meerbek
ABSTRACT: This article presents findings of a study concerned with destination image of Kyrgyzstan. As online narratives provide an important source for destination image formation, the present study analyzed a total of 360 travel blogs about the country with a computer-assisted program, Leximancer 4.5. Analysis suggested that the image of Kyrgyzstan as a destination is mainly associated with nomadic culture and natural resources. It also indicated that foreign visitors view the country as a transit, not a final destination, and that the critical aspect of the country's image is its poor transportation infrastructure. The article encourages destination marketers and policymakers to take relevant measures to create positive images of the country. Additionally, it recommends that natural resources as well as cultural endowment should be capitalized on, and transportation infrastructure should be improved.